Numerical Simulation of a Down-hole Heat Exchanger: An Application to a Case Study in Central Italy. (November 2016) - Carlini, Maurizio; Allegrini, Elena; Castellucci, Sonia
Abstract: According to many recent European and National Directives, ambitious targets are increasingly set so as to ensure a clean and sustainable future for the forthcoming generations. In order to change from being predominantly fossil fuelled to being fuelled by locally available sources, low-enthalpy geothermal installations for heating and cooling buildings can be successfully used, such as Down-hole Heat Exchangers (DHEs). Although in the last decades DHEs have been studied extensively, both numerically and experimentally, some aspects still need to be further investigated, namely the interaction between aquifer, well, and the DHE itself. Thus, the present paper investigates the thermal behaviour of a DHE in Central Italy, considering one-year experimental campaign. The numerical simulation is carried out by the finite-element program Comsol Multiphysics and is validated by the experimental data concerning the values of temperature within the DHE at a specific depth. In more detail, it is implemented by a model describing the U-tube and the surrounding aquifer. Although in most of the simulation only a single domain is taken into account, the adjacent medium is here implemented as a boundary condition. The results for the computational domain are presented in terms of temperature, highlighting that the numerical simulation is an efficient method to accurately reproduce the temperature pattern within the DHE.